Common Adverse Events Associated with the Use of Ribavirin for Severe Acute Respiratory Syndrome in Canada - Knowles, Sandra R. (Clin Infect Dis, 2003)
Although information on efficacy and adverse drug reactions is lacking, ribavirin has been used empirically for the treatment of severe acute respiratory syndrome (SARS). We report common adverse events in 110 patients with suspected or probable SARS who were treated with ribavirin. Sixty-one percent of the patients had evidence of hemolytic anemia, and hypocalcemia and hypomagnesmia were reported in 58% and 46% of patients, respectively.